Tax Accounting for Livestock: Mother or meat/Capital or revenue? - Fullarton, Lex; Pinto, Dale (Thomson Reuters New Zealand, 2021)
Australia is experiencing cataclysmic weather events largely due to rising atmospheric temperatures caused by greenhouse gas emissions — climate change. A consequence of droughts, floods, fires, tempests and family disasters is the sale or loss of valuable stud stock. In normal trading circumstances, these animals would not be sold as trading stock. However, the sale of pastoral properties can be beyond the will of the owners for a raft of reasons. Presently, the receipts from the sale of ALL animals sold as part of a primary production business are considered to be income, according to ordinary concepts of the Australia Taxation Office (ATO), and taxed at ordinary income tax rates. This paper considers the value of animals included in the sale of rural properties in Australia. It argues that the provisions of the Income Tax Assessment Act 1997 (ITAA 1997) are being misinterpreted by tax administrators and tax professionals. Considering the sale of ALL animals traded during the sale of a pastoral lease or farm as revenue denies vendors of concessions permitted under the capital gains tax provisions. This paper examines the income and capital gains tax implications on the sale of animals in conjunction with the sale of pastoral and farming properties in Australia. The distinction between classifying expenditure by an enterprise to be on items of a capital or a revenue nature has long been argued. Generally, in accounting terms, expenditure is considered to be of a capital nature if the benefit of the purchased asset is applied to more than one accounting period.